New-onset angina pectoris: initial characteristics and results of a 6 to 12-month follow-up - Ananich, V A; Gratsianskii, N A; Karasev, A V; Olferiev, A M; Nechaev, A S; Yanus, V M; Oganov, R G (Cor et vasa, 1990)
173 patients, aged 46.8 years on the average, were examined in the first 3 months after onset of angina pectoris. 97% of them presented at least one of risk factors (smoking, arterial hypertension, overweight, dyslipoproteinaemia), in 79% two or more risk factors were present simultaneously. A greater than 70% stenosis of one coronary artery was present in 51%, in 10% the stenosis was smaller than 70%, in 4% the coronary arteries were intact. In 131 patients without a history of myocardial infarction, vasospastic angina, overweight, and simultaneous presence of 3 or 4 risk factors occurred more frequently than in 42 patients with a history of myocardial infarction. In the first month, complications were registered only in patients with unstable angina pectoris (5 out of 41, i.e., 12%). During the later period of follow-up in 102 patients, complications occurred in 5% and complete clinical remission was registered in 35%. In patients with remission, positive exercise tests and haemodynamically significant stenoses of 2 or 3 coronary arteries were less frequently found on initial examination than in patients with sustained angina pectoris.
Keywords: senioři; elektrokardiografie; Remission Induction; angina pectoris; Middle Aged; mužské pohlaví; Adult; Follow-Up Studies; následné studie; Electrocardiography; ženské pohlaví; Humans; Angina Pectoris; Hemodynamics; hemodynamika; lidé středního věku; indukce remise; rizikové faktory; dospělí; Female; Aged; Risk Factors; lidé; Male